2021
DOI: 10.1097/rlu.0000000000003815
|View full text |Cite
|
Sign up to set email alerts
|

Portal Biliopathy and Cavernous Transformation of the Portal Vein Revealed by 68Ga-FAPI PET/CT

Abstract: A 47-year-old man presented with right upper abdominal pain for 1 month. Contrast-enhanced CT revealed hilar bile duct stenosis with dilatation of the intrahepatic bile ducts, and his serum CA19-9 and CA242 levels were significantly elevated. 18 F-FDG and 68 Ga-FAPI PET/CTwere performed for differential diagnosis. 18 F-FDG PET/CT showed only mild FDG uptake in the hepatic hilum. Astonishingly, in 68 Ga-FAPI PET/CT, intense radioactivity was presented on the same region, which indicated massive fibroblasts aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In this case, the relatively novel radiotracer, 68 Ga-labeled FAPI, was successful in assessing primary Klatskin tumor and avoided the well-known false-negative pitfall of the more traditional 18 F-FDG, particularly for the histological mucinous subtype 1,2 . Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically 3–9 . According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts 10,11 .…”
supporting
confidence: 64%
See 1 more Smart Citation
“…In this case, the relatively novel radiotracer, 68 Ga-labeled FAPI, was successful in assessing primary Klatskin tumor and avoided the well-known false-negative pitfall of the more traditional 18 F-FDG, particularly for the histological mucinous subtype 1,2 . Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically 3–9 . According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts 10,11 .…”
supporting
confidence: 64%
“…1,2 Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically. [3][4][5][6][7][8][9] According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts. 10,11 This, combined with FAPI's significantly lower background (liver) uptake, results in excellent target-to-background ratios and, as a result, improved sensitivity for not only the primary tumor, but also metastatic nodal and distant carcinomatosis.…”
Section: Figurementioning
confidence: 99%
“…A final laparotomy resulted in a diagnosis of portal vein biliary lesions caused by cavernous portal degeneration. In this case, the uptake rate of portal cholangiopathy caused by cavernous portal degeneration was higher on 68 Ga-FAPI PET/CT than on 18 F-FDG PET/CT ( 82 ). A 57-year-old man with a history of colon cancer resection showed enhanced FAPI uptake in the gallbladder wall with a central area of reduced signal on 68 Ga-FAPI PET/CT.…”
Section: Organs Of the Abdominal Cavitymentioning
confidence: 68%
“…The gallbladder typically shows low physiologic FAPI uptake. Reported nononcologic FAPI uptake includes IgG4-related sclerosing cholangitis (average SUV max : 9.4) 37 and portal biliopathy (SUV max : 8.2) due to cavernous transformation of the portal vein 79 …”
Section: Fapi Pet Oncologic and Nononcologic Incidental Findingsmentioning
confidence: 99%